2019
DOI: 10.1016/j.dib.2019.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on controlled production of polyhydroxyalkanoate-based microbead using double emulsion solvent evaporation technique

Abstract: A significant source of microplastics is from the usage of microbeads in the market since petrochemical plastic bead is a material used in cosmetic scrubs. A possible way to counteract the problem is by the substitution of synthetic plastic to natural biodegradable polymer. Polyhydroxyalkanoate (PHA) is a general class of thermoplastic microbial polymer and it is the best alternative to some petrochemical plastics due to its biodegradability. Some PHA has earned its way into cosmetic application due to its bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…PHA can also revolutionise established pharmacological procedures, and protein immobilisation on biopolymers could broaden its emerged applications. This innovative, biodegradable, and biocompatible polymer is a promising future option, with the potential to partially replace synthetic petroleum-based plastics even in cosmetics [ 162 ].…”
Section: Challenges Opportunities and Way Forwardmentioning
confidence: 99%
“…PHA can also revolutionise established pharmacological procedures, and protein immobilisation on biopolymers could broaden its emerged applications. This innovative, biodegradable, and biocompatible polymer is a promising future option, with the potential to partially replace synthetic petroleum-based plastics even in cosmetics [ 162 ].…”
Section: Challenges Opportunities and Way Forwardmentioning
confidence: 99%
“…An oil/water solvent evaporation technique adapted to encapsulation of PT and REGO in PLGA-NPs (Zhao et al., 2014 ; Shao et al., 2017 ; Govindasamy et al., 2019 ). Briefly, DOPA-coated PT (50 µg) cores and REGO (50 µg) were added to a PLGA-NP solution in CHCl 3 (100 mg in 350 µl).…”
Section: Methodsmentioning
confidence: 99%
“…They were discovered to be porous materials with tiny grains linked in a regular pattern [ 139 ]. SEM pictures of poly(3-hydroxybutyrate) [P(3HB)] homopolymer produced by Bacillus megaterium UMTKB-1 and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) P(3HB-co-3HV) copolymer produced by Massilia haematophila UMTKB-2 showed that the microbeads were between 8 and 56 m in size [ 140 ].…”
Section: Characterization Of Phamentioning
confidence: 99%